2019
DOI: 10.1039/c9nr00709a
|View full text |Cite
|
Sign up to set email alerts
|

A facile phase transformation strategy for fabrication of novel Z-scheme ternary heterojunctions with efficient photocatalytic properties

Abstract: With increasing pollution of water resources and demand for hydrogen energy, photocatalysis, as a “green chemistry” technology, has attracted great attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…In present context, solar energy is the supreme resource to combat energy and environment related issues. With an aim to enhance the utilization of solar energy, the field of photocatalysis for water splitting and pollutant degradation have gained interest [1][2][3][4] . Further, the demand for exciting materials that serve selectivity, have directed the focus towards the 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…In present context, solar energy is the supreme resource to combat energy and environment related issues. With an aim to enhance the utilization of solar energy, the field of photocatalysis for water splitting and pollutant degradation have gained interest [1][2][3][4] . Further, the demand for exciting materials that serve selectivity, have directed the focus towards the 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental and energy issues are the two major factors hindering the sustainable development of human society. Photocatalysis is considered one of the effective routes to solve the above two issues [1][2][3][4][5][6][7]. Since the pioneering work of Fujishima and Honda in 1972 [8] on photoelectrochemical water splitting over a TiO2 electrode, photocatalytic H2 generation has been investigated as one of the most promising routes to convert solar energy into available chemical energy [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ternary HSs consisting of three semiconductors have attracted considerable attention. For example, Xie et al [39] prepared new ternary ZnTiO3/Zn2Ti3O8/ZnO HSs with high efficiency for photocatalytic hydrogen evolution and polluted water treatment. Jang et al [40] fabricated ternary CdS/ZnIn2S4/TiO2 HSs with excellent photoelectrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, they reported that the Zn2Ti3O8 was transformed to ZnTiO3 when the calcination temperature was increased to 600 °C. Another group reported that calcining zinc oxide (ZnO) and titanium dioxide (TiO2) with the mol ratio of 2:3 at 750 °C was able to obtain the Zn2Ti3O8 phase [16]. Accordingly, the Zn:Ti mol ratio of 2:3 was used in the present work to obtain the Zn2Ti3O8 phase.…”
Section: Introductionmentioning
confidence: 94%